Investigation on the stability, thermal characteristics and natural convection heat transfer in oil-based nanofluids. - ILYAS, SUHAIB UMER (2018)
Thermal oils are widely used as cooling media in heat transfer processes. However, their potential has not been utilised exquisitely due to low thermal properties. The addition of nanoparticles in thermal oil can improve thermal properties.